Factors Caused for The Existence of Bakuke Art in Non Java Communities - Nopianti, Heni; Heri Sunaryanto; Hainun Annisa (Talenta Publisher, 2022)
Research aims to analyze the factors that cause the existence of BAKUKE (Barongan KudaKepang) Javanese art in the community that is not a traditional javanese territory. The approach usedin research is qualitative descriptive with informant determination techniques that are done purposivesampling. The data collection techniques used are observation, in-depth interviews and Focus GroupDiscussion, and documentation. The data obtained is then reduced, sorted and recorded and verified toobtain the validity of the data in order to answer the research formulation. Research producesinformation that 'Candra Kirana' is the art of Barongan Kuda Kepang Jawa Tribe in Dusun Kebun Ubican exist in areas that are not Java because (1) function factors, as a medium of entertainment in theeyes of the public; (2) Cultural inheritance value factors attached to the community of players whohave Javanese blood; (3) Myth factors, in the form of treatment myths in people who experiencesupernatural diseases, awake from invisible creatures, prohibitions when watching shows usingumbrellas, watching from the top of fences or trees, doing 'suits' and myths for cultural heirs such as ifcultural heritage is not lived it will get a 'catastrophe'.